SCA CLARIFIES THE TERM “MOTOR VEHICLE” IN ROAD ACCIDENT FUND ACT 56 OF 1996: The Road Accident Fund v Mbele [2020] ZASCA 72 - Darren Subramanien (Obiter, 2022)
The Supreme Court of Appeal (SCA) in The Road Accident Fund v Mbele [2020] ZASCA 72 (SCA judgment) had to decide whether a large industrial vehicle called a Reach Stacker was a motor vehicle as contemplated in section 1 of the Road Accident Fund Act 56 of 1996 (the Act). This judgment is important, not only because it paves the way for the respondent and others like the respondent to claim compensation from the Road Accident Fund in cases of injury or death, but also, because it provides clarity on the test that the court uses to determine whether a vehicle in question is a motor vehicle as contemplated in the Act. The features, purpose and intended use of the vehicle in question play a pivotal role in the determination of whether a vehicle is a motor vehicle. The SCA indicated that the Reach Stacker in question was equipped with full road-going lighting, including tail lights, indicators, brake lights and reverse lights. Furthermore, it was fitted with windscreen wipers and washers, a hooter, and a handbrake. According to the court, it was clear from its features that the Reach Sacker fitted the description of a “motor vehicle” as defined in the Act.